2020
DOI: 10.21203/rs.3.rs-35351/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reviewing the Ecological Evidence-Base for Management of Emerging Tropical Zoonoses: Kyasanur Forest Disease in India as A Case Study

Abstract: Background Zoonotic diseases disproportionately affect poor tropical communities. Transmission dynamics of zoonoses are complex, involving communities of vector and animal hosts, with human behaviour and ecosystem use altering exposure to infected vectors and hosts. This complexity means that efforts to manage and prevent human spillover are often hampered by a poor ecological evidence base and intervention strategies tend to focus on humans (e.g. vaccination, preventative drug treatment). However, integrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 80 publications
(109 reference statements)
0
22
0
Order By: Relevance
“…Of the variety of information sources cited by households, we found that informal sources were important channels for disseminating KFD-related information. Admittedly, the health department's information education and communication (IEC) outreach activities were also severely constrained by logistical and personnel challenges, which highlights the need for strengthening technical capacities and more importantly, cross-sectoral collaboration as a means of complementing existing management efforts [52,22,16]. There is some evidence that tailoring risk communication with potential adaptation pathways (including leveraging relevant traditional practices) and presenting these in relatable and locally appropriate languages could potentially incentivise widespread uptake of disease information [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the variety of information sources cited by households, we found that informal sources were important channels for disseminating KFD-related information. Admittedly, the health department's information education and communication (IEC) outreach activities were also severely constrained by logistical and personnel challenges, which highlights the need for strengthening technical capacities and more importantly, cross-sectoral collaboration as a means of complementing existing management efforts [52,22,16]. There is some evidence that tailoring risk communication with potential adaptation pathways (including leveraging relevant traditional practices) and presenting these in relatable and locally appropriate languages could potentially incentivise widespread uptake of disease information [16].…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of meaningful community engagement in public health interventions has been recognised [13], to date, there is limited empirical examination of the role of disease information in shaping the adaptive capacity of vulnerable groups to emerging zoonotic disease risks [14]. The complex and changing disease dynamics (shaped by the ecology and evolutionary biology of infectious disease vectors and hosts [1,15,6] has meant that access to up-to-date information remains crucial to successful adaptation of communities [16]. We thus address this knowledge gap by exploring how the delivery and access to disease information influences the adaptive capacity of small-holder farmer and tribal communities to emerging zoonotic disease risks, focussing on the context of India.…”
Section: Introductionmentioning
confidence: 99%
“…Of the variety of information sources cited by households, we found that informal sources were important channels for disseminating KFD-related information. Admittedly, the health department's information education and communication (IEC) outreach activities were also severely constrained by logistical and personnel challenges, which highlights the need for strengthening technical capacities and more importantly, cross-sectoral collaboration as a means of complementing existing management efforts [51,22,16]. There is some evidence that tailoring risk communication with potential adaptation pathways (including leveraging relevant traditional practices) and presenting these in relatable and locally appropriate languages could potentially incentivise widespread uptake of disease information [16].…”
Section: Discussionmentioning
confidence: 99%
“…10,12]. Considering that the social and livelihood organisation of forest communities are conditioned around 'secure' forest access, existing and future interventions on zoonoses management must strongly re ect this reality [1,16]. As evidenced in our results, the seeming scepticism regarding messages on the voluntary avoidance of forest and/ or compliance with imposed forest restrictions (in a bid to reduce the risk of forest communities' exposure to KFD) re ects the operational limitations of 'top-down' and paternalistic approaches of the bureaucracy on the ground.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation